Pemikiran Ekonomi Syariah dan Prinsip - Prinsip Hukum dalam Penerapan Akad Mudharabah Muqayyadah - Ade Suryawirawan; Ahmad Hasan Ridwan (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study examines the philosophy of Islamic economics and the legal principles underlying the implementation of the mudharabah muqayyadah contract in Islamic financial institutions. The mudharabah muqayyadah contract is a form of partnership contract involving the shahibul maal (capital owner) and mudharib (business manager), with provisions limited to a certain scope, so that the implementation of this contract must be based on sharia principles that regulate all forms of financial transactions. This study focuses on how ethical values in Islam are integrated with the legal principles of sharia contracts, particularly in maintaining fair relations between the two parties. Through a normative qualitative approach, data were collected from classical and contemporary literature as well as regulations applicable in the Islamic financial sector. The results show that the mudharabah muqayyadah contract is a manifestation of maqashid al-shariah in economic practice, which aims to safeguard assets, uphold justice, and create balance in economic transactions. The legal principles applied in this contract include freedom of contract, good faith, and fairness, which serve to ensure transparency, accountability, and justice between the parties involved. However, the biggest challenges in implementing the mudharabah muqayyadah contract are the aspects of supervision and compliance with sharia principles, as well as technical practices that are often influenced by conventional systems. Therefore, this study recommends the need to strengthen education on sharia philosophy for practitioners in the Islamic financial sector, as well as the need for regulatory harmonization to ensure the fair implementation of the contract, in accordance with the transcendental values taught in Islam. Furthermore, harmonization of regulations governing the mudharabah muqayyadah contract is also crucial to create uniformity in practice across Islamic financial institutions. Clear and firm regulations will reduce the potential for misinterpretation that can lead to bias against the interests of one party.